SP10.2.12 Information Sustainability: The revitalisation and upcycling of 373, 342 historic surgical pathology records into the contemporary electronic patient record in one UK NHS Hospital Trust. (28th October 2021) - Rahman, Fatima; Hales, Alan; Cable, David; Burrill, Keith; Bateman, Adrian; Rew, David
Abstract: Aims: Surgical and Cellular pathology ('e-pathology') record sets are a valuable data resource with which to populate the Electronic Patient Record (EPR). Accessible reports, even decades old, can be of great value in contemporary clinical decision making and as a resource for longitudinal clinical research. They commonly identify the operation, the location and the pathology, even if not to modern reporting standards. Methods: Since 2010, we have built and implemented a timeline structured EPR for the 'whole-of-life' visualisation of the electronic documents (e-Docs) of 2.5M+ patients on our Master Index. Prior to this project, our earliest e-Docs dated to 1995. We tracked down 373, 342 inert e-pathology reports from our legacy Ferranti (1990-1997) and Masterlab (1997-2004) systems. These were uploaded into our active file servers, following appropriate data quality and patient identity reconciliation checks. Results: We have progressively restored 373, 342 previously inaccessible e-pathology records to clinical use and to immediacy of access, and in the process extending our "addressable EPR" back to 1990 for living and deceased patients. This process has also allowed us to populate and validate an EPR-integral breast cancer data system of 20, 000 cases with e-pathology records dating back to 1990. Conclusions: The sustainable revitalisation of old e-pathology reports into a timeline structured EPR creates preserves and upcycles the investment in pathology reporting which is otherwise progressively lost to clinical use. E-pathology records provide reliable, life-long evidence of critical transition points in individual lives and disease progression for clinical and research use, when they can be instantly accessed.